Exploring the Courage and Generosity of Women in the Select Novels of Kavita Kane (International Journal of Food and Nutritional Sciences, 2019)
This paper explores the courage and generosity of women as a daughter, sibling, companion,and mother with reference to the select novels of Kavita Kane, Sita’s Sister and Menaka’sChoice. The characters Urmila and Menaka sacrifice their own well-being standing in supportof their respective families.